46. ACADEMIC MOTIVATION OF NURSING STUDENTS AT VINH MEDICAL UNIVERSITY AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current academic motivation of nursing students at Vinh Medical University and identify some related factors. Research subjects and methods: Cross-sectional descriptive study on 626 nursing students at Vinh Medical University from August 2024 to April 2025. The AMS-C28 toolkit uses a 7-point Likert scale for assessments of academic motivation.Results: In 616 students, the proportion of students in the "Poor academic motivation" group accounted for 65.7%, and those with good academic motivation accounted for only 34.3%. Most of the types of academic motivation have an average score above 4. The external motivation score to determine the highest average is 5.4±1.1, and the non-motivation score has the lowest value of 2.2±1.2 in the types of motivation. Some factors such as self-confidence, encouragement from family and friends, image of nurses in society, easy-to-understand teaching methods, encouragement and guidance from teachers in learning and training programs have a statistically significant relationship with academic motivation.Conclusion: The rate of students with academic motivation is 34.3%. There is a relationship between academic motivation and self-confidence, encouragement from family and friends, image of nurses in society, easy-to-understand teaching methods, encouragement and guidance from teachers in learning and training programs.
Keywords: Learning motivation; nursing students; related factors